2013
DOI: 10.1136/emermed-2012-201831
|View full text |Cite
|
Sign up to set email alerts
|

Trauma survival prediction in Asian population: a modification of TRISS to improve accuracy

Abstract: The present study has demonstrated that (1) having the Age variable being dichotomised (cut-off at 55 years) as in the eTRISS, but with the application of a local dataset-derived coefficients give better TRISS survival prediction in Asian blunt trauma patients; (2) improved performance are found with certain recategorisation of the Age variable and (3) the accuracy can further be enhanced if the Age effect is taken to be linear, with the application of local dataset-derived coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 62 publications
4
22
0
Order By: Relevance
“…In recent years, based on reports discussing the possibilities that changes to various coefficients, such as use of actual age and changes to the 55‐year age classification, have on the accuracy of the regression model and the background of the remarkable improvement in the survival rate of patients with unstable vital signs on admission, reports have acknowledged that there is less need for RR and BP as variables, particularly at the Level 1 trauma center . These results also support the verification results attained herein.…”
Section: Discussionsupporting
confidence: 83%
“…In recent years, based on reports discussing the possibilities that changes to various coefficients, such as use of actual age and changes to the 55‐year age classification, have on the accuracy of the regression model and the background of the remarkable improvement in the survival rate of patients with unstable vital signs on admission, reports have acknowledged that there is less need for RR and BP as variables, particularly at the Level 1 trauma center . These results also support the verification results attained herein.…”
Section: Discussionsupporting
confidence: 83%
“…Comparing ISS and RTS means in deceased and recovered patients showed a statistically significant difference between the two groups, with RTS mean significantly lower in deceased patients than in recovered patients and ISS mean higher in deceased patients than in recovered patients. The results of all studies in this field showed a direct relationship between ISS and injury severity and an inverse relationship between RTS and injury severity (31)(32)(33) Norouzi et al (11) conducted a study on traffic-injured patients in Ardebil in which RTS mean for deceased patients was 5.29 and 7.62 for recovered patients. Also, ISS mean was 29.65 in deceased patients and 13.98 in recovered patients.…”
Section: Discussionmentioning
confidence: 99%
“…The TRISS based on Multiple Trauma Outcome Study (MTOS) is the largest database of descriptive contemporary injury information; the survival probability norms use the RTS, ISS, patient age and injury mechanisms 37. Modification may provide better prediction 38. The lower ISS and higher TRISS during Phase 3 than Phases 2 and 1 may lead to the suspicion that the improvement in survival was due to the lesser severity of injury in Phase 3.…”
Section: Discussionmentioning
confidence: 99%